Automatização de um tribômetro pin on disc - Teodoro, Fabricio Cassanho (2023)
The objective of this work is the automation/control of a tribometer, this equipment is used for research and study on phenomena related to friction. For this, a bibliographic review of concepts related to the components that make up this equipment was carried out, such as: electric drive (motor, frequency inverter and control circuits), electronic components dedicated to reading variables (temperature, rotation and load cell sensors), data processing (microcontroller) and computational interface. Next, an electrical panel was built that could group all the electronic components to meet the needs of the tribological experiment. An operating logic for the equipment was also developed and translated into programming language to be used in the microcontroller. Subsequently, the entire set was connected and tested, operating satisfactorily within the pre-established conditions.